Diversity and antibacterial potential produced by marine endophytic fungi by submerged fermentation from Buton Island, Indonesia - Isti’anah Ismi; Tarman Kustiariyah; Heri Suseno Sugeng; Nugraha Roni; Effendi Irzal; Lee Wen-Chien; Lukitaningsih Endang; Manggau Marianti A.; Sari Rodiah Nurbaya (BIO Web of Conferences)
This study investigated the diversity and antibacterial potential of marine endophytic fungi from Buton Island, Indonesia. This study focused on identifying fungi capable of producing bioactive compounds effective against Vibrio harveyi. 32 fungal isolates were obtained from various marine samples. Aspergillus terreus (WB 1-2) exhibited the highest antibacterial activity. The growth dynamics of these fungi were analyzed, emphasizing the importance of the log phase for secondary metabolite production. Environmental conditions and mechanical agitation were found to significantly influence growth and metabolite yield. These findings highlight the potential of marine endophytic fungi as sources of novel antimicrobial agents, suggesting promising opportunities for biotechnological and pharmaceutical advancements. This study underscores the untapped potential of marine fungi for the development of new antibiotics.